2020
DOI: 10.1007/s11098-020-01520-0
|View full text |Cite
|
Sign up to set email alerts
|

Is the world a heap of quantum fragments?

Abstract: Fragmentalism was originally introduced as a new A-theory of time. It was further refined and discussed, and different developments of the original insight have been proposed. In a celebrated paper, Jonathan Simon contends that fragmentalism delivers a new realist account of the quantum state-which he calls conservative realism-according to which: (i) the quantum state is a complete description of a physical system, (ii) the quantum (superposition) state is grounded in its terms, and (iii) the superposition te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…3). 59 It has recently been suggested that Jonathan Simon's fragmentalist approach to interpreting the quantum state vector (Simon, 2018) is actually "Everettian Quantum Mechanics in disguise" or at any rate "dangerously close" to it (Iaquinto & Calosi, 2021, p. 2017. This is incorrect.…”
Section: Interpreting St and Gtmentioning
confidence: 99%
“…3). 59 It has recently been suggested that Jonathan Simon's fragmentalist approach to interpreting the quantum state vector (Simon, 2018) is actually "Everettian Quantum Mechanics in disguise" or at any rate "dangerously close" to it (Iaquinto & Calosi, 2021, p. 2017. This is incorrect.…”
Section: Interpreting St and Gtmentioning
confidence: 99%
“…There has been an earlier attempt at a fragmentalist interpretation of quantum mechanics: Simon[34] has proposed that a superposition of quantum states corresponds to a collection of fragments of the physical world. This proposal faces serious difficulties, however[25].…”
mentioning
confidence: 99%